GAC (MOMORDICA COCHINCHINENSIS) EXTRACT AND ANTIOXIDANT POTENTIAL IN OSTEOARTHRITIS: AN EVIDENCE-BASED MEDICINE OVERVIEW (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on the antioxidant profile of gac (Momordica cochinchinensis) extracts and their potential role in osteoarthritis management.Methods: We searched PubMed/PMC, Scopus, and major publishers (1/2019-10/2025) for studies on gac composition and bioactivity, and on oxidative stress in osteoarthritis, including in vitro, in vivo and human data on carotenoids (lycopene, β-carotene) and related phytochemicals. Inclusion criteria were peer‑reviewed studies on gac components/extracts or antioxidants relevant to osteoarthritis pathophysiology; exclusions were non‑scholarly items and studies with inadequate outcome reporting.Results: Gac aril is exceptionally rich in carotenoids and tocopherols and shows strong antioxidant and anti‑inflammatory activity; optimized extraction enhances carotenoid yield. Oxidative stress contributes to chondrocyte senescence, cartilage matrix degradation, and synovitis in osteoarthritis. Lycopene reduces IL‑1β‑induced inflammatory signaling and matrix catabolism in chondrocytes and alleviates osteoarthritis features in animal models; lower circulating lycopene correlates with greater knee osteoarthritis pain/disability. Meta‑analytic evidence suggests nutraceutical antioxidants modestly improve pain and function in osteoarthritis, though heterogeneity is substantial. No randomized trials of gac in osteoarthritis were identified.Conclusion: Gac extract is biologically plausible as an adjunctive antioxidant strategy for osteoarthritis based on composition and mechanistic data, but clinical efficacy remains unproven. Standardized extract characterization, dose‑finding, and rigorously designed RCTs in knee osteoarthritis are priorities.
Keywords: Gac, Momordica cochinchinensis, osteoarthritis, antioxidants, lycopene.